The Effect of Changes in Lower Incisor Inclination on Gingival Recession - Gulen Kamak; Hasan Kamak; Hakan Keklik; Hakan Gurcan Gurel (The Scientific World Journal)
Aim. Orthodontic treatment may promote development of recessions. The mechanism by which orthodontic treatment influences occurrence of recessions remains unclear. The aim of this study was to test the hypothesis that a change of mandibular incisor inclination promotes development of labial gingival recessions. Materials and Methods. The study sample comprised dental casts and lateral cephalograms obtained from 109 subjects before orthodontic treatment (Tb) and after orthodontic treatment (Ta). Depending on the change of lower incisor inclination during treatment, the subjects were divided into three groups: Retroclination (R), Stable Position (S), and Proclination (P). The presence of gingival recessions of mandibular incisors and clinical crown heights were assessed on plaster models. Results and Conclusions. From Tb to Ta, Inc_Incl showed a statistically significant change in the R, P, and S groups (p<0.05). Increase of clinical crown heights of the lower incisors (42, 4, and 31) was not statistically significant in any group. The only statistically significant intergroup difference was the greater increase of the clinical crown height of tooth number 32 in the P group in comparison with the R group (p=0.049). The change of lower incisor inclination during treatment did not lead to development of labial gingival recessions in the study sample.